Changes in Parents’ Meta-Emotion Philosophy from Preschool to Early Adolescence. - Stettler, Nicole; Katz, Lynn Fainsilber (Parenting: Science & Practice)
Objective.To explore how components of parent meta-emotion philosophy may change over the course of children’s development.Design.Forty mothers and 38 fathers completed the Parent Meta-Emotion Interview (PMEI; Katz & Gottman, 1986) when their children were 5, 9, and 11 years old.Results.Parents’ coaching of children’s negative emotions increased from 5 to 11 years. Awareness and acceptance of children’s negative emotions decreased between 5 and 9 years but increased overall between 5 and 11 years.Conclusions.This study provides evidence that parents’ attitudes and philosophies around emotion socialization change over time, and change appears to be linked to children’s developmental stage.